Health risk assessment of heavy metals in soils and food crops from a coexist area of heavily industrialized and intensively cropping in the Chengdu Plain, Sichuan, China - Liu, Qing; Li, Xiaohui; He, Lei (Frontiers in Chemistry, 2022)
Environmental pollution caused by rapid industrial activities are becoming increasingly drastic, particularly its impact on soil and plant health. The present study was conducted to investigate the heavy metal(loid) (As, Cd, Cu, Hg, Pb and Zn) concentrations in soils and food biomass crops and estimate the potential health risks of metals to humans via consumption of contaminated food biomass crops from Shifang, a periurban agricultural areas in the Chengdu Plain, Sichuan, China. Results revealed the soils have been experiencing a substantial accumulation of heavy metals, especially for Cd, with a mean of 0.84 mg kg-1, about 6 times higher than the background values, of which 98% exceeded the pollution warning threshold of the China Soil Environmental Quality Standards. 78% of all the grain part failed the national food standard for Cd. No significantly positive relationships between metals levels in food biomass crops and in the corresponding soils, indicated metals enrichment in soils were not entirely reflected to crops contaminant burdens. Estimated daily intake (EDIs) of all the metals except for Pb, exceeded the oral reference dose (RfD) or the minimal risk levels recommended by USEPA and ATSDR. Target hazard quotients (THQs) of all the metals except for Cd was less than 1 indicated that potential health risk to the local inhabitant originated mainly from Cd exposure via cereals consumption. Mitigation strategies to curtail Cd-contaminated soils and crops Cd burdens need careful tailoring to meet the needs of health and safety in this region.